Dialektika Multikultural Muslim Indonesia: Konflik dan Kerukunan Beragama dalam Perspektif Alquran - Muhaemin . (Journal of Islamic Civilization, 2021)
The multicultural life of the Indonesian Muslim community potential for conflict. To prevent and minimize the emergence of conflict, the Quran as a holy book offers a solution in maintaining harmony. This article aims to analyze the conflicts and their motives that occur in the Quran as well as offer solution to conflicts that occur in society based on the verses of harmony. The method used in this research is qualitative-thematic with content analysis theory. This theory is useful for analyzing the words in the verse of the Quran that explain conflict and harmony, so that the meaning and moral message of the verse can be reached. The results of the study are verses of the Quran in respecting differences and diversity and accepting social reality as an unavoidable fact. This is explained in QS. al-Hujurat verse 13, QS. Hud verse 118-119, QS. Asy-Syura verse 8 dan QS. Yunus verse t 99.